(untitled) (Sebha University Conference Proceedings, 2025)
To enhance khella plant growth, yield components, chromone content, and economic value, a field experiment was conducted at the Farm of the Faculty of Agriculture, Al-Azhar University, Assiut, Egypt, over the two successive seasons of 2022/2023 and 2023/2024. The different humic acid levels (0.0, 5.0, 10.0, and 15.0 kg/ha), different seaweed extract rates (0.0, 1.0, 3.0, and 6.0 ml/L), and their combination treatments were studied. The obtained results were pointed out that utilizing humic acid (HA) at 15 kg level per hectare significantly increased khella growth (plant height, branches number and herb fresh and dry weights/ plant), fruit yield per plant and hectare and khellin, visnagin and total chromone percentages compared to control end the other levels under study. The highest values of growth traits, yield components, and chromone percentages were noticed when khella plants were sprayed with seaweed extract (SE) at 3 ml/l compared to the control. Generally, the best combination treatment between humic acid levels and seaweed extract rates regarding khella yield components was 15 kg/ha of HA + 6 ml/l of SE, compared to the other combination treatments under study in both seasons.